2012
DOI: 10.4236/jbise.2012.59068
|View full text |Cite
|
Sign up to set email alerts
|

Protoporphyrin IX photobleaching of subcellular distributed sites of leukemic HL60 cells based on ALA-PDT <i>in vitro</i>

Abstract: The leukaemia cells HL60, incubated in 10 mM/ml ALA (5-aminolevulinic) for 4 hours, were carried an experimental research with fluorescent probes in photodynamic therapy (PDT) based on ALA by using PDT reaction room (The average fluence rate of the 412 nm source was 5 mW/cm<sup>2</sup>). Cells viability were determined using a Cell Counting Kit-8 (CCK-8) assay, and PpIX Photobleaching of subcellular distributed sites of HL60 cells in vitro were investigated by fluorescence spectra acquired during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Photoinduced decarboxylation, driven by electron acceptance from a neighboring Glu, has previously been assumed for GFP and DsRed . X‐ray structure analysis of the bleached KillerRed chromophore revealed at least partial breakage of the conjugated π‐system at the methylene bridge .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Photoinduced decarboxylation, driven by electron acceptance from a neighboring Glu, has previously been assumed for GFP and DsRed . X‐ray structure analysis of the bleached KillerRed chromophore revealed at least partial breakage of the conjugated π‐system at the methylene bridge .…”
Section: Discussionmentioning
confidence: 83%
“…Since the lowering of fluorescence results from a direct attack of ROS or singlet oxygen on the photosensitizer molecules, it reflects the efficiency of the photochemical reaction and can potentially predict the outcome of the therapy. The relation between photobleaching, singlet oxygen and the PDT response has been investigated in models in vitro and in vivo for a range of photosensitizers including Photofrin , Photogem , mTHPC , 5‐ALA induced protoporphyrine IX and benzoporphryin‐derivative BPD . In the experiments with mTHPC in vitro Jarvi et al showed that photobleaching can be used as a PDT dose metric, but this approach failed under hypoxic conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of photodynamic diagnosis and therapy (PDD and PDT) for cancer diagnosis and treatment are becoming more widespread due to its minimally invasive and highly selective nature (1–5). The photodynamic technique utilizes the photochemical reaction of a photosensitizer that is initiated when a specific wavelength of light is absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and treatment efficacy of the PDD and PDT is dependent on the monitoring, dosimetry estimation and understanding of the mechanism of the photodynamic (PD) processes. Photobleaching and photoproducts formations are phenomena essential in studying these factors, and the study of these phenomena during the PD processes has been increasing (2,7–9).…”
Section: Introductionmentioning
confidence: 99%